STRmix™ collaborative exercise on DNA mixture interpretation. (May 2019) - Bright, Jo-Anne; Cheng, Kevin; Kerr, Zane; McGovern, Catherine; Kelly, Hannah; Moretti, Tamyra R.; Smith, Michael A.; Bieber, Frederick R.; Budowle, Bruce; Coble, Michael D.; Alghafri, Rashed; Allen, Paul Stafford; et al.
Highlights: Inter-laboratory study with 174 participants using STRmix™. CE analysis settings resulted in larger differences in LR than PG software. Differences in log( LR ) due to MCMC variation were less than one order of magnitude. Abstract: An intra and inter-laboratory study using the probabilistic genotyping (PG) software STRmix™ is reported. Two complex mixtures from the PROVEDIt set, analysed on an Applied Biosystems™ 3500 Series Genetic Analyzer, were selected. 174 participants responded. For Sample 1 (low template, in the order of 200 rfu for major contributors) five participants described the comparison as inconclusive with respect to the POI or excluded him. Where LR s were assigned, the point estimates ranging from 2 × 10 4 to 8 × 10 6 . For Sample 2 (in the order of 2000 rfu for major contributors), LR s ranged from 2 × 10 28 to 2 × 10 29 . Where LR s were calculated, the differences between participants can be attributed to (from largest to smallest impact): varying number of contributors ( NoC ), the exclusion of some loci within the interpretation, differences in local CE data analysis methods leading to variation in the peaks present and their heights in the input files used, and run-to-run variation due to the random sampling inherent to all MCMC-based methods. This study demonstrates a high level of repeatability and reproducibility among the participants. For those results that differed from the mode, the differences in LR were almost always minor or conservative.